EKSPERIMENTASI MEDIA PEMBELAJARAN KOMIK EDUKASI PENGENALAN ANGKA BAGI ANAK USIA DINI - Isnaini Nur Azizah; Leli Fertiliana Dea; Muhammad Yusuf; Mai Zuniati; A Muslimin (Yaa Bunayya : Jurnal Pendidikan Anak Usia Dini, 2021)
Media is a component that affects the learning process. Because the media is a tool in channeling messages (material) to students. Lately, there have been many development researches that have resulted in a product, however the effectiveness of the resulting product still needs to be tested. This study aims to test products that have been produced before, in the form of educational math comics on number recognition for early childhood. The research method used is the Quasi Experiment (quasi-experiment). The results of this study indicate that there is a positive influence of educational comics learning media on early childhood mathematical communication dispositions. This effect is known in the t-test, that the disposition of students' mathematical communication after being given educational comic learning media and those not given educational comics learning media, the results are known> where in this t-test it is known that t-count = 7.896 while t-table = 1.7171 at a significance of 5% .